THE SEASONAL VARIABILITY OF CPUE AND CATCH-AT-SIZE DISTRIBUTION OF TROLL AND HANDLINE TUNA FISHERIES LANDED IN LABUHAN LOMBOK - Bram Setyadji; Hety Hartaty; Siti Mardlijah (Indonesian Fisheries Research Journal, 2016)
Troll and hand line tuna fisheries is one of the major fishing gears landed in Labuhan Lombok coastal fishing port (PPP Labuhan Lombok) west Nusa Tenggara Barat province.  Both fisheries are strongly associated with fish aggregating devices (FAD’s). The main fishing ground is Indian Ocean southern part of this province.  Several source of data has been collected regularly. Data analysis comprised of monthlycatch and effort data samples based onport monitoring program during 2012 to 2015. The result showed the diclining of CPUE of yellow fin and skipjack tuna presumably related to fishing intensity of fleets and its variability that landed in PPP Labuhan Lombok.  The increasing CPUE of skipjack tuna in 2014 was predicted due to increasing aggregation around the FADs. Constrasting seasonal fishing index pattern between yellowfin and skipjack tuna foundin 4-month cycles, started in January.A length-weight relationship suggested that yellowfin tuna caught bysmall-scale fisheries were performing allometric growth pattern (b=2.963, r2=0.9737).